The Urgency of Civil Law Reform in Responding to the Development of Artificial Intelligence in Automatic Contracts - Khuan, Hendri (PT. Hafasy Dwi Nawasena, 2025)
The rapid development of Artificial Intelligence (AI) technology has led to the emergence of smart contracts that revolutionize conventional contract law practices. However, Indonesia's civil law system, which still relies on the Civil Code (KUHPer), has yet to accommodate digital entities or address the validity of AI-generated contracts. Furthermore, there is no clear regulation regarding legal liability for errors or damages caused by AI in the implementation of automated contracts. This research aims to analyze the urgency of Indonesian civil law reform in addressing the rise of AI-based contracts and to provide normative recommendations for developing technology-adaptive laws. This study uses a normative juridical method with statutory, conceptual, and comparative legal approaches, examining regulations in Indonesia and other jurisdictions such as the European Union and Singapore. The study finds that Indonesia’s current Civil Code is inadequate to address the complexities of smart contracts, particularly regarding the legal status of AI as a non-human actor, the validity of automated agreements, and liability for AI-driven decisions. The discussion emphasizes the importance of legally recognizing smart contracts and reformulating civil law norms to include digital legal subjects, clear validation mechanisms for AI-generated contracts, and the principles of prudence and accountability. In conclusion, reforming civil law is a strategic necessity to ensure legal certainty, uphold justice, and support the sustainable development of Indonesia’s digital economy.